Drums and Guns - Burnside, Iain; Hanratty, Conor (My University, 2016)
The powerful combination of music and literature and the collective talents of three institutions are the foundation stones for an exciting collaborative project led by renowned pianist and Guildhall professor Iain Burnside. Bringing together artists from the Guildhall School, Royal Irish Academy of Music, Dublin and the Juilliard School, New York, Drums and Guns is a devised piece which explores conflict in war and the impact it has on families left behind. This fresh and engaging production commemorates both World War I and the 1916 Easter Rising in Dublin.
Devised by Iain Burnside. Directed by Iain Burnside and Conor Hanratty. Victoria Newlyn: movement director. Sunny Smith: designer.
Keywords: Music; Songs with piano; World War, 1914-1918; Ireland - History - Easter Rising, 1916